Economic challenges and costs of reintegrating the Donbas region in Ukraine - Peter Havlik; Artem Kochnev; Olga Pindyuk (The Vienna Institute for International Economic Studies (wiiw), 2020)
This study provides a systematic assessment of the costs of the ongoing armed conflict in the Donbas region of Ukraine. By combining the pre-war geographical distribution of fixed capital with data on battle intensity, survey evidence on household damage in the conflict-affected areas and novel data on the macroeconomy of certain areas of the Donetsk and Luhansk regions, the report estimates the minimum reconstruction costs of the region at USD 21.7 billion. On the basis of the composition of the costs, the study argues that the government's main focus should be on restoring the basic institutions that are usually taken for granted in most economies: the markets and state capacity. The study proposes the key features of a reconstruction plan to help achieve this goal. This plan - assuming a lasting ceasefire is being observed - involves a continuation of the reform path in order to achieve sustainable and inclusive economic growth, to attract both foreign and domestic investments, improve the well-being of Ukrainian citizens and increase the opportunity costs of conflict. The systematic collection and dissemination of data on the Donbas region is essential. Ukraine should strive for balanced trade with the rest of the world. Last but not least, ensure that the peace settlement is durable. In the case of the Donbas this would mean an additional agreement that would not substitute the Minsk II Agreement but would both help to implement and complement it.
Keywords: F50; F51; H12; H56; O52; I38; Q34; 330; conflict economics; political economy; international conflict; Ukraine; restoration; Donbas